Spectroscopic properties and photodynamic effects of new lipophilic porphyrin derivatives: Efficacy, localisation and cell death pathways - Kramer-Marek, Gabriela (2006)
Photodynamic therapy (PDT) and photodynamic diagnostics (PDD) of cancer are based on the use of non-toxic dyes (photosensitisers) in combination with harmless visible light. This paper reports physicochemical properties, cell uptake, localisation as well as photodynamic efficiency of two novel lipophilic porphyrin derivatives, suitable for use as PDT sensitisers. Both compounds are characterised by high quantum yield of singlet oxygen generation which was measured by time-resolved phosphorescence. Photodynamic in vitro studies were conducted on three cancer cell lines. Results of cell survival tests showed negligible dark cytotoxicity but high phototoxicity. The results also indicate that cell death is dependent on energy dose and time following light exposure. Using confocal laser scanning microscopy both compounds were found to localise in the cytoplasm around the nucleus of the tumour cells. The mode of cell death was evaluated based on the morphological changes after differential staining.